The Concept Of Fiscal Decentralization And Policy Management In Federal Countries - Abduladheem Alwash, Lamyaa Haleem (Opción, 2019)
States shall ensure that the jurisdiction of the judiciary shall be divided among the different courts the legislator defines the definition according to which the jurisdiction of each jurisdiction is determined and the legislator intervenes to define the type of jurisdiction or type of courts that serve one jurisdiction. This distribution although it had the greatest impact on improving the au- thority and facilities of the judiciary, but it was at the time as a starting point for legal problems between arbitrators arising from conflict in defining their jurisdiction